PENGARUH LABA PER SAHAM, PENDAPATAN, DAN TOTAL ARUS KAS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Go Publik di Bursa Efek Indonesia Sektor Industri Barang Konsumsi dan Aneka Industri periode 2015-2016) - Akhmad Firdan Rakhman; Nur Ainy (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
Money managers clearly have a fiduciary duty to investigate before they invest client funds. The purpose of this per stock is, Income and Total cash flow the value of change both simultaneously and partial. This study employes a method of casual testing or case. Financial base was taken from a financial report of entities affiliated with the industrial facilities of the industrial food and a wide variety of industry in 2015-2016. The analysis data used a double regression analysis the result of a partial research directed that the income and total cash flow have an effect on the vale of the company. But the profit per share has no influence on the value of the company. The result of the research simultaneously indicate that a simultaneously return of the profit per share, the total cash flow and income has an effect the value of the company Keywords: Earnings per Sahre, Revenue, Total cash flow, the value of the company